Pengaruh Komunikasi Organisasi dan Gaya Kepemimpinan Terhadap Kinerja Karyawan pada Industri Ritel Smartphone di Kota Cirebon - Sarah Naflah Nurfadhilah; Muhamad Alwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of leadership style and organizational communication on employee performance. This study used a quantitative approach with a survey method, where data were collected through questionnaires distributed to respondents. The number of respondents in this study was 104 employees. The data analysis technique used was multiple linear regression analysis using the SPSS program, preceded by validity tests, reliability tests, and classical assumption tests. The results showed that leadership style influences employee performance. Furthermore, organizational communication also influences employee performance. Simultaneously, leadership style and organizational communication influence employee performance, meaning that both independent variables together can improve employee performance. These findings indicate that implementing an appropriate leadership style and effective organizational communication are crucial for improving employee performance. This research is expected to contribute to organizations as a consideration in making human resource management policies, particularly in developing leadership and organizational communication systems to improve employee performance.